Low Transfer of Tacrolimus and Its Metabolites into Colostrum of Graft Recipient Mothers - Kociszewska-Najman, Bozena (Nutrients, 2018)
Currently, the majority of neonates born to organ recipient mothers on chronic immunosuppressive therapy are formula fed. However, over the past few years, evidence has grown, suggesting that breastfeeding might be possible and beneficial. We designed a study assessing the transfer of tacrolimus into the colostrum of posttransplant mothers. We assessed the amount of tacrolimus and its metabolites, M-1 and M-3, that would be ingested by the breastfed neonates. Concentrations of tacrolimus and its metabolites were measured in colostrum from 14 posttransplant mothers as well as in venous cord blood and venous blood of the neonates. Test material analysis was performed by liquid chromatography coupled with mass spectrometry (LC/MS). The amount of ingested formula was registered, which allowed for estimation of the amount of tacrolimus and its metabolites that would be ingested by breastfed infants. The mean amount of tacrolimus that would be ingested by the neonates in maternal milk was 151.4 ng/kg/24 h (standard deviation SD ± 74.39); metabolite M-1: 23.80 ng/kg/24 h (SD ± 14.53); and metabolite M-3: 13.25 ng/kg/24 h (SD ± 9.05). The peak level of tacrolimus and metabolite M-1 in colostrum was noted 8 h after an oral dose (3.219 ng/mL SD ± 2.22 and 0.56 ng/mL SD ± 0.60, respectively) and metabolite M-3 after 6 h (0.29 ng/mL SD ± 0.22). Low concentrations of tacrolimus and its metabolites, M-1 and M-3, in colostrum show that neonates will ingest trace amounts of the drug. Further studies are required to fully assess the safety of breastfeeding by posttransplant mothers.